Editor's Choice – Peri-Operative Outcomes of Carotid Endarterectomy are Not Improved on Dual Antiplatelet Therapy vs. Aspirin Monotherapy: A Systematic Review and Meta-Analysis. (April 2022) - Ku, Jerry C.; Taslimi, Shervin; Zuccato, Jeffrey; Pasarikovski, Christopher R.; Nasr, Nathalie; Chechik, Ofir; Chisci, Emiliano; Bissacco, Daniele; Larrue, Vincent; Rabinovich, Yefim; Michelagnoli, Stefano; Settembrini, Piergiorgio G.; et al.
Abstract : Objective: A systematic review and meta-analysis of the peri-operative outcomes of carotid endarterectomy (CEA) on dual antiplatelet therapy (DAPT) vs. aspirin monotherapy was carried out, to determine optimal peri-operative management with these antiplatelet agents. Data sources: The Web of Science, Pubmed, and Embase databases were searched from inception to July 2021. The corresponding authors of excluded articles were contacted to obtain additional data for possible inclusion. Review methods: The main outcomes included ischaemic complications (stroke, transient ischaemic attack [TIA], and transcranial Doppler [TCD] measured micro-emboli), haemorrhagic complications (haemorrhagic stroke, neck haematoma, and re-operation for bleeding), and composite outcomes. Pooled estimates using odds ratios (ORs) were combined using a random or fixed effects model based on the results of the chi square test and calculation of I 2 . Results: In total, 47 411 patients were included in 11 studies, with 14 345 (30.2%) receiving DAPT and 33 066 (69.7%) receiving aspirin only. There was no significant difference in the rates of peri-operative stroke (OR 0.87, 95% confidence interval [CI] 0.72 – 1.05) and TIA (OR 0.78, 95% CI 0.52 – 1.17) despite a significant reduction in TCD measured micro-emboli (OR 0.19, 95% CI 0.10 – 0.35) in the DAPT compared with the aspirin monotherapy group. Subgroup analysis did not reveal any significant difference in ischaemic stroke risk between patients with asymptomatic and symptomatic carotid artery stenosis. DAPT was associated with an increased risk of neck haematoma (OR 2.79, 95% CI 1.87 – 4.18) and re-operation for bleeding (OR 1.98, 95% CI 1.77 – 2.23) vs. aspirin. Haemorrhagic stroke was an under reported outcome in the literature. Conclusion: This meta-analysis found that CEA while on DAPT increased the risk of haemorrhagic complications, with similar rates of ischaemic complications, vs. aspirin monotherapy. This suggests that the risks of performing CEA on DAPT outweigh the benefits, even in patients with symptomatic carotid stenosis. The overall quality of studies was low, and improved reporting of CEA outcomes in the literature is necessary.